A multi-disciplinary approach for research and presentation of Bracara Augusta’s archaeological heritage - Martins, Manuela (2000)
The purpose of this paper is to present an archaeological information system and multimedia application used to record, manage and diffuse the data provided by the excavations conducted, since 1976, in Braga, Portugal, and related to the “Urban Rescue Project of Bracara Augusta”. The Geographical Information System built to manage and process the archaeological information (SIABRA), created by a team from the Archaeology Unit of Minho University, which was responsible for the Project, is presented. A natural result and advantage of this System is to simplify and enhance spatial analysis and data articulation related to the main buildings which have already been found, as well as the urban interpretation. One further advantage is the three dimensional model reconstruction, where a specialist (archaeologist, architect, urbanist) can analyse and visualise complex and diachronic information concerning the Roman town, in order to simplify the global understanding of buildings, their reconstruction phases and the general relationships between them. The development of virtual environments reproducing archaeological sites, such as the Roman town of Bracara Augusta, can be considered as an important and powerful tool for facilitating the research of specialists and improving heritage consciousness.